RELEVANSI ALIRAN FILSAFAT PROGRESIVISME DENGAN IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR - Latif, Azminudin; Darwanti, Asri; Wahyuni, Sri; Sumardjoko, Bambang; Fauziati, Endang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This article discusses the relevance of the progressivism philosophy to the implementation of the Kurikulum Merdeka (Independent Curriculum) in elementary schools. This research is a type of library research or literature study, seeking theoretical references related to the cases or issues found. The author uses a descriptive analysis method with a hermeneutic approach to describe and interpret the data obtained. The results show that the relevance of the progressivism philosophy to the implementation of the Kurikulum Merdeka in elementary schools is highly significant and mutually supportive. The Kurikulum Merdeka, which emphasizes freedom and democracy in learning, aligns with the principles of progressivism that prioritize change, development, and the improvement of education quality. This concept focuses on character building of students through project-based learning, supporting the values of Pancasila, and giving students the freedom to choose learning methods that suit their environment.